Crystallographic and computational study of 1-(arylamino)-1, 2, 3-triazole-4-carbohydrazides. Issue 11 (5th December 2014) - Seth, Saikat Kumar; Lee, Vannajan Sanghiran; Yana, Janchai; Zain, Sharifuddin M.; Cunha, Anna C.; Ferreira, Vitor F.; Jordão, Alessandro K.; de Souza, Maria C. B. V.; Wardell, Solange M. S. V.; Wardell, James L.; Tiekink, Edward R. T.
Abstract : The influence of substituents on the formation of supramolecular synthons is described. Abstract : The crystallography of mono- p -substituted derivatives of 1-(arylamino)-1, 2, 3-triazole-4-carbohydrazides, 1 (X = H), 2 (F), 3 (Cl) and4 (Br), and a 2, 5-dichloro (5 ) analogue, shows the molecular structures to be similar. Distinct hydrogen bonding patterns based on N–H⋯N and N–H⋯O are observed in their crystal structures with1, having two independent molecules comprising the asymmetric unit, displaying one pattern, 2 and5 another, and3 and4 yet another. Geometry optimisation calculations indicate that any conformational differences in the solid state do not persist in the gas-phase and that no influence of the substituents is seen on the geometric parameters. A natural population analysis, for both experimental and optimised structures, shows that the charge on the triazole-N3 atom is at a maximum for1, as opposed to2–5, an observation correlated with its distinctive packing based around a supramolecular synthon not seen in the other structures. For the molecules having electronegative substituents, molecular electrostatic potentials show that the energies of the amine-H4n atoms are reduced for2 and5, compared to3 and4 . A further distinction in2–5 is indicated by the Hirshfeld surface analysis which highlights the importance of π⋯π interactions in2 and5, i.e. with the more electronegative substituents. Clearly, there is interplay between various factors but all correlated with the influence of the electronegativity of the substituent(s).